Current Advancements in Sactipeptide Natural Products - Chen, Yunliang; Wang, Jinxiu; Li, Guoquan; Yang, Yunpeng; Ding, Wei (Frontiers in Chemistry, 2021)
Ribosomemally synthesized and posttranslationally modified peptides (RiPPs) are a growing class of natural products that benefited from genome sequencing technology in the past two decades. RiPPs are widely distributed in nature and show diverse chemical structures and rich biological activities[1-3]. Despite the various structural characteristics of RiPPs, they follow a common biosynthetic logic: a precursor peptide containing an N-terminal leader peptide and a C-terminal core peptide is translated from one single gene, and then the precursor peptide undergoes a series of steps of modification, transport, and cleavage to form a mature natural product with specific activities. Sactipeptides (Sulfur-to-alpha carbon thioether cross-linked peptides)[1, 4] belong to RiPPs that show various biological activities such as antibacterial, spermicidal, and hemolytic properties[5-10]. Their common hallmark is an intramolecular thioether bond that crosslink the sulfur atom of a cysteine residue to the α-carbon of an acceptor amino acid which was catalyzed by a rSAM enzyme [5]. This review summarizes recent achievements concerning the discovery, distribution, structural elucidation, biosynthesis and application prospects of sactipeptides.